A Glossary of Terms for Mega Thinking and Planning. Issue 6 (5th July 2018) - Kaufman, Roger
Abstract: Professionals are responsible for the results, consequences, and payoffs they deliver. This requires a renewed focus on the evidence‐based decisions. Critical for this is a consistency in language that leaves no confusion regarding the value added for individuals, organization, and society. This glossary provides a basis for defining and achieving success in the future through a definition of terms that focuses on the results and payoffs for internal and external clients instead of the processes, activities, and interventions we routinely apply.